Quality of Government Cohesion Across EU Regions: Success or Failure - Karahasan, Burhan Can (Routledge Journals, Taylor & Francis Ltd, 2026)
Regional differences in institutions is a threat for political and economic integration. In this paper, we analyse the institutional convergence across regions of the European Union (EU). Preliminary results show that there is continuous improvement fostering institutional convergence. However, heterogeneity analyses point-out that the speed of institutional development is influenced by the enlargement phases of the union. Additional results indicate that the regions of the Central and Eastern European (CEE) countries and the southern regions belonging to Greece and Spain experience faster institutional convergence. Accordingly, the enlargement process, fostering further heterogeneity, is an important element to improve the institutional quality of the new EU members. However, temporal convergence trends show that the dynamics of institutional convergence shift over time, reflecting the non-stationary evolution of success-failure cases.
Keywords: Convergence; Eu; Quality of Government; Spatial Heterogeneity; O43, R11, R12, R50